A Novel Splicing Mutation in the FBN2 Gene in a Family With Congenital Contractural Arachnodactyly - Xu, Peiwen; Li, Ruirui; Huang, Sexin; Sun, Menghan; Liu, Jiaolong; Niu, Yuping; Zou, Yang; Li, Jie; Gao, Ming; Li, Xiaolei; Gao, Xuan; Gao, Yuan (Frontiers in Genetics, 2020)
Congenital contractural arachnodactyly (CCA) is an extremely rare monogenic disorder in humans, and the prevalence of CCA is estimated to be less than 1 in 10,000 worldwide. CCA is characterized by arachnodactyly, camptodactyly, contrature of major joints, scoliosis, pectus deformities, and crumpled ears. Mutations in FBN2 (produces Fibrillin-2) are responsible for causing this disease. A family with CCA was investigated in this study and a novel variant c.3724+3A>C (also known as IVS28+3C>G) in FBN2 was found in the nine patients from the family, but was not found in seven unaffected relatives. Reverse transcription-PCR (RT-PCR) and cDNA sequencing data showed that the exon 28 was cut off in the FBN2 gene. The FBN2 c.3724+3A>C variant led to an in-frame deletion during transcription, which eventually triggered CCA in the Chinese family.